Does K-line (−) in the Neck-flexed Position Predict Surgical Outcome of Cervical Spondylotic Myelopathy?: Results of a Multivariate Analysis After Muscle-preserving Selective Laminectomy. Issue 19 (1st October 2020) - Nori, Satoshi; Aoyama, Ryoma; Ninomiya, Ken; Suzuki, Satoshi; Anazawa, Ukei; Shiraishi, Tateru
Abstract : Study Design: A retrospective single-center study. Objective: The aim of this study was to investigate the influence of the K-line in the neck-flexed position (flexion K-line) on the surgical outcome after muscle-preserving selective laminectomy (SL) for cervical spondylotic myelopathy (CSM). Summary of Background Data: Development of CSM is associated with dynamic factors and cervical alignment. The flexion K-line, which reflects both dynamic and alignment factors, provides an indicator of surgical outcome after posterior decompression surgery for patients with ossification of the posterior longitudinal ligament. However, the value of the flexion K-line for patients with CSM has not been evaluated. Methods: Our study group included 159 patients treated with SL for CSM. Patients were divided into a flexion K-line (+) group and a flexion K-line (−) group. The influence of the flexion K-line on radiological and surgical outcomes was analyzed, with multivariate analysis conducted to identify factors affecting the surgical outcome. Results: Patients in the flexion K-line (−) group were younger ( P = 0.003), had a less lordotic cervical alignment (pre-and postoperatively, P < 0.001), a smaller C7 slope (pre-and postoperatively, P < 0.001), and a greater mismatch between the C7 slope and the C2-C7 angle (preoperatively, P = 0.047; postoperatively, P = 0.001). The postoperative increase in Japanese Orthopedic Association (JOA) score and the JOA score recovery rate (RR) were lower for the flexion K-line (−) than for the K-line (+) group ( P < 0.001 and P < 0.001, respectively). On multivariate regression analysis, the flexion K-line (−) ( β = −0.282, P < 0.001), high signal intensity (SI) changes on T2-weighted image (WI) combined with low SI changes on T1-WI in the spinal cord ( β = −0.266, P < 0.001), and older age ( β = -0.248, P = 0.001) were predictive of a lower JOA score RR. Conclusion: The flexion K-line may be a useful predictor of surgical outcomes after SL in patients with CSM. Level of Evidence: 4 Abstract : The K-line (−) in the neck-flexed position, preoperative high signal intensity (SI) changes on T2-weighted image (WI) combined with low SI changes on T1-WI in the spinal cord, and older age were predictors of a poor functional recovery after muscle-preserving selective laminectomy in patients with cervical spondylotic myelopathy.